Rapid cultivation of aerobic granular sludge in a continuous flow reactor. Issue 4 (December 2015) - Long, Bei; Yang, Chang-zhu; Pu, Wen-hong; Yang, Jia-kuan; Liu, Fu-biao; Zhang, Li; Cheng, Kai
Graphical abstract: Highlights: A novel continuous flow aerobic granular reactor was introduced. A new cultivation method in continuous flow reactor was proposed. Mechanism of rapid aerobic granulation was investigated. Abstract: Aerobic granular sludge (AGS) was successfully cultivated in a double column cyclic aerobic granular reactor (DCCAGR) within 18 days by inoculating with 30% (w/w) mature aerobic granules and 70% activated sludge, while granulation process and reactor performance was investigated in the continuous flow reactor. The AGS cultivated was white or pale yellow, while granule's SVI, average particle size, granulation rate, extracellular polymeric substances, polysaccharides/proteins ratio and water content were about 46 mL/g, 1.2 mm, 92%, 37 mg/g MLVSS, 1.4 and 98.3% on the 20th day. Observed from the microscopic structure of the cultivated AGS, a large number of microorganisms tightly adhered together inhibited inside the granules, including coccus, bacillus and protozoa. Finally, effluent chemical oxygen demand, total inorganic chemical demand, ammonium nitrogen and total phosphorus of the system were 33 mg/L, 8.46 mg/L, 7.3 mg/L and 1.26 mg/L, and their removal rates were 97%, 88%, 90% and 87% respectively. Effective hydraulic selection pressure can be created in DCCAGR, while inoculated AGS had positive significance to the agglomeration of other flocculent sludge, which greatly reduced the startup time and consumption of mature aerobic granules.